2013
DOI: 10.1186/gm510
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of whole genome amplification of single circulating tumor cells enriched by CellSearch and sorted by FACS

Abstract: BackgroundTumor cells in the blood of patients with metastatic carcinomas are associated with poor survival. Knowledge of the cells’ genetic make-up can help to guide targeted therapy. We evaluated the efficiency and quality of isolation and amplification of DNA from single circulating tumor cells (CTC).MethodsThe efficiency of the procedure was determined by spiking blood with SKBR-3 cells, enrichment with the CellSearch system, followed by single cell sorting by fluorescence-activated cell sorting (FACS) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 19 publications
2
66
0
1
Order By: Relevance
“…A different flow-sorting protocol for isolation of CellSearch CTCs was very recently described by Swennenhuis et al (15 ). For 10 tested clinical CellSearch samples of patients with lung cancer, the authors reported a markedly lower CTC detection rate (mean efficiency, 43% vs 102%; median efficiency, 41% vs 83%).…”
Section: Ctcs (mentioning
confidence: 99%
See 1 more Smart Citation
“…A different flow-sorting protocol for isolation of CellSearch CTCs was very recently described by Swennenhuis et al (15 ). For 10 tested clinical CellSearch samples of patients with lung cancer, the authors reported a markedly lower CTC detection rate (mean efficiency, 43% vs 102%; median efficiency, 41% vs 83%).…”
Section: Ctcs (mentioning
confidence: 99%
“…The very low concentration of CTCs and the unpredictable number of "contaminating" hematopoietic cells always cocaptured as background by the CellSearch system hamper direct downstream molecular analyses, and hence further purification and isolation of the rare CTCs is required. Initial data indicated that flow-sorting approaches might be suitable for CTC purification (15 ), but efficient protocols have been lacking. Here, we present a protocol to efficiently purify single CTCs captured with the CellSearch circulating tumor cell kit that enables their further comprehensive genetic analysis on a single-cell level.…”
Section: © 2014 American Association For Clinical Chemistrymentioning
confidence: 99%
“…One of the major challenges in CTC research concerns the number of CTCs that have to be analyzed to be able to outline the profile of the clones that drive disease in cancer, with conflicting results being provided by case reports involving both CTC and ctDNA analysis in metastatic breast cancer patients [96,97]. However, in recent years, efforts have been made to develop multiple markers to increase the yield of CTCs [98][99][100], and to improve their amplification [101][102][103] and sequencing techniques [104][105][106].…”
Section: Discussionmentioning
confidence: 99%
“…An inevitable step therefore is to pick and isolate the single CTCs in individual tubes or as a pure CTC fraction for genomic analysis. Methods used to isolate single cell for individual analysis in combination with CellSearch-enriched CTCs: Micromanipulation [113], ALS Cellselector [114], the Silicon Biosystems DEPArray [115][116][117][118], FACS [28,119,120], and the Punch system using self-seeding Microwell Chips [121]. This step seems a minor intermediate part of the whole workflow but is crucial for the end result.…”
Section: Collection Of the Immunomagnetically Enriched And Fluorescenmentioning
confidence: 99%